Understanding e-Government Failure from an Actor-Network Perspective : The Demise of the Thai Smart ID Card /: The Demise of the Thai Smart ID Card. (2014) - (Senior lecturer in information systems), Gao, Ping; Gunawong, Panom
No abstract available